The role of organizational communication in enhancing organizational loyalty - Al-Qahtani, Yasser Hassan Saleh (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed at learn about the role of organizational communication in enhancing the organizational loyalty of employees of the joint stock companies in Abha. In order to achieve these objectives, the study adopted descriptive analytical method, and the researcher designed a questionnaire as a main tool for collecting the necessary data, which were applied to a sample of workers in the companies contributing to the father (59) individuals. The results of the study reached several results, the most important of which is that there is a role for organizational communication in enhancing the organizational loyalty of the employees of the joint stock companies in Abha. The results of the arithmetic averages showed that the sub-hypothesis is not accepted, which states that: "There is an average level of organizational communication between presidents and subordinates In the companies participating in the city of Abha, "and the sub-hypothesis that states:" There is an average level of organizational loyalty among the employees of the companies in the city of Abha, "and the sub-hypothesis that states:" There are statistically significant differences in the relationship between organizational communication and loyalty Organization Due to demographic characteristics (sex - age - education level - the nature of the job - years of experience)". The study recommended a number of recommendations, the most important of which is that every company of any kind and size must work on developing its communications methods and surround everything that might impede this process, whether in terms of the worker’s psychological or regulatory environment, in order to strengthen the organizational loyalty of the employees of these companies , And to increase the awareness of officials of the joint stock companies of the importance of the role of communication in enhancing the organizational loyalty of employees and the reflection on the completion and development of these companies.